A wideband and flat-gain of an amplifier by using zirconia-based erbium-doped fiber (Zr-EDF) for single pass pperation - Markom, A.M.; Ahmad, Harith; Harun, Sulaiman Wadi (Penerbit UTM Press, 2016)
An amplification for single pass operation was demonstrated by using Zirconia-based erbium-doped fiber (Zr-EDF). 1 m is the optimum length due to overall high gain and minimal noise figure from 1520 nm to 1620 nm. The highest gain is 28.62 dB at 1555 nm with the input signal and pump power are fixed at -30 dBm and 130 mW, respectively. At input signal -10 dBm, a wide and flat-gain of 19.36 dB is obtained with very small variation gain of 0.27 dB from 1530 nm to 1570 nm. Meanwhile, the noise figure for both input signals were maintained below than 12 dBm for the specific regions.